A Dirhoda‐Heterocyclic Carbene. Issue 11 (29th January 2020) - Barnett, Harrison J.; Hill, Anthony F.
Abstract: The linear μ‐carbido complex [Rh2 (μ‐C)Cl2 (dppm)2 ] (dppm=bis(diphenylphosphino)methane) reacts with dimethylacetylene dicarboxylate (DMAD) to afford [Rh2 (μ‐C)(μ‐DMAD)Cl2 (dppm)2 ], which features a bent RhCRh linkage (124.7°) that might be described as a dirhoda‐heterocyclic carbene, as demonstrated by coordination to further metal centers. Abstract : The first example of an isolable bent μ‐carbido complex, that behaves in a manner reminiscent of a heterocyclic carbene is described.